Prostate cancer diagnosis: an immunological aspects - S. V. Popov; R. G. Guseinov; I. N. Orlov; V. V. Protoshchak; O. N. Skryabin; P. A. Babkin; F. A. Bagrov; A. S. Katunin; A. G. Martov; V. L. Schukin (Вестник урологии, 2019)
Introduction. Contemporary diagnosis of prostate cancer is crucial to the patient’s further fate. Difficulties in the histological verification of the final diagnosis and false-negative results of biopsy research are often associated with the similarity of the prostate adenocarcinoma`s micromorphological picture and its benign lesions.Purpose of the study. Comprehending the possibilities of immunohistochemical identification of tumor cells and the basal epithelial layer of prostate glandular structures in prostate cancer suspected cases.Materials and methods. A biopsy material was taken from 134 patients. Prostate adenocarcinoma was verified by routine histological examination in 72 samples, in 62 samples there were no signs of malignant transformation. Subsequently, immunohistochemical analysis of biopsy specimens was performed using antibodies to α-methylacyl-CoA racemase, nuclear p63 protein and high-molecular cytokeratin.Results. The AMACR-positive reaction of malignant cells and a negative reaction of the basal epithelium to nuclear p63 protein antibodies and high-molecular cytokeratin were detected during prostate adenocarcinoma.Conclusion. If prostate cancer is suspected, immunohistochemical assays with monoclonal antibodies to AMACR, p63 and high-molecular cytokeratin greatly facilitate the detection of adenocarcinoma.